2013
DOI: 10.1105/tpc.113.111849
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of a Phloem Membrane Protein Encoded by NHL26 Alters Phloem Export and Sugar Partitioning in Arabidopsis

Abstract: The complex process of phloem sugar transport involves symplasmic and apoplasmic events. We characterized Arabidopsis thaliana lines ectopically expressing a phloem-specific gene encoding NDR1/HIN1-like26 (NHL26), a putative membrane protein. NHL26 overexpressor plants grew more slowly than wild-type plants, accumulated high levels of carbohydrates in mature leaves, and had a higher shoot biomass, contrasting with slower root growth and a lower seed yield. Similar effects were observed when NHL26 was overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 104 publications
(128 reference statements)
4
23
0
Order By: Relevance
“…Our results show that carrot root enlargement can be attributed to the differentiation of VC, a cylindrical meristematic tissue that gives rise to the secondary xylem toward the inner part, and to SP toward the outer part. We also observed SGs deposition in the carrot root; its distribution is similar to that of sugar and carotene, which are located in the cortex (Vilaine et al 2013). …”
Section: Discussionsupporting
confidence: 63%
“…Our results show that carrot root enlargement can be attributed to the differentiation of VC, a cylindrical meristematic tissue that gives rise to the secondary xylem toward the inner part, and to SP toward the outer part. We also observed SGs deposition in the carrot root; its distribution is similar to that of sugar and carotene, which are located in the cortex (Vilaine et al 2013). …”
Section: Discussionsupporting
confidence: 63%
“…The lower emission of TPS23/27 terpene products in ndr1-1 is intriguing, and clearly shows that factors other than TPS23/27 transcript levels are of importance. Recently accumulation of NHL26, another NDR1/HIN1-like membrane protein with structural similarities to LEA proteins, was shown to affect permeability of plasmodesmata and sugar transport in the phloem (Vilaine et al, 2013). A more comprehensive understanding of root-associated microorganisms and plant responses including long-distance signal trafficking is likely to be achieved using new high-throughput technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified increase in expression of NDR1/ HIN1-like related genes during CLas or CLam infection in C. sinensis (Lu et al, 2013;Mafra et al, 2013). Vilaine et al (2013) showed that arabidopsis overexpressing NHL26 accumulated high levels of carbohydrate in phloem tissue of mature leaves, higher shoot biomass, contrasting with slower root growth and a lower seed yield. HLB infected citrus species manifest similar characteristics, which have been considered a consequence of phloem blockage (Johnson et al, 2014;Wang & Trivedi, 2013).…”
Section: Microscopical Analysesmentioning
confidence: 99%